Transcriptional investigation of the toxic mechanisms of perfluorooctane sulfonate in rats based on an RNA-Seq approach. (July 2023) - Wang, Tianrun; Zhao, Xuying; Liu, Tianze; Zhang, Jiguang; Qiu, Jing; Li, Mei; Weng, Rui
Abstract: Perfluorooctane sulfonate (PFOS) was widely used in industrial applications before it was listed as a persistent organic pollutant by the Conference of the Parties in the Stockholm Convention in 2009. Although the potential toxicity of PFOS has been studied, its toxic mechanisms remain largely undefined. Here, we investigated novel hub genes and pathways affected by PFOS to gain new conceptions of the toxic mechanisms of PFOS. Reduced body weight gain and abnormal ultra-structures in the liver and kidney tissues were spotted in PFOS-exposed rats, indicating successful establishment of the PFOS-exposed rat model. The transcriptomic alterations of blood samples upon PFOS exposure were analysed using RNA-Seq. GO analysis indicates that the differentially expressed gene-enriched GO terms are related to metabolism, cellular processes, and biological regulation. Kyoto encyclopaedia of gene and genomes (KEGG) and gene set enrichment analysis (GSEA) were conducted to identify six key pathways: spliceosome, B cell receptor signalling pathway, acute myeloid leukaemia, protein processing in the endoplasmic reticulum, NF-kappa B signalling pathway, and Fc gamma R-mediated phagocytosis. The top 10 hub genes were screened from a protein–protein interaction network and verified via quantitative real-time polymerase chain reaction. The overall pathway network and hub genes may provide new insights into the toxic mechanisms of PFOS exposure states. Graphical abstract: Image 1 Highlights: PFOS-exposed rat model successfully established. Transcriptomic alterations of rats upon PFOS exposure analysed using RNA-seq. Six pathways identified as potential toxic mechanisms of PFOS. Ten hub genes screened as key genes of PFOS toxicity. The immune system of PFOS-exposed rats significantly affected by PFOS exposure.